Effects of different salinity levels on the survival and growth of marble goby, Oxyeleotris marmoratus larvae - Senoo, Shigeharu; Sok Hui, Sow; Mukai, Yukinori (Japan Aquicultural Research Group, 2008)
The marble goby, Oxeyeleotris marmoratus is the highest priced freshwater fish in Southeast Asia. However, the stable seed production technique has not yet been established due to the high mortality occuring in the larval stage. To solve the problem, 2 rearing experiments were conducted with Brachinus sp. feeding in different salinity levels (Sal.). In experiment 1, the effects of different Sals on the survival and growth were investigated in the larval stage, during the period from 1 to 40 days after hatching (d AH). In Experiment 2, the larval stage was divided int o4 periods (1-10, 11-20, 21-30 and 31-40 sd AH), and the optimum SaL for each period was determined. The optimum SaL was 10 ppt through out the whoole larval stage. It was understood that the most important period of the salanity adjustment was in 1-10 d AH for the larval rearing. Although 10 ppt is the optimum SaL in the later rearing periods of 11-20, 21-30, and 31-40 d AH, larval rearing was possible in both freshwater and seawater. The successful utilization of Brachionus sp as feed for freshwater fish O. marmoratus was substantial progress for stable mass seed production in the future.